PENERAPAN STRATEGI PEMBELAJARAN INTERAKTIF UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS V SD NEGERI 2 TANJUNG MEDANG - Sari, Riska; Lazim N, Lazim N; Antosa, Zariul (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The background of the research in SD Negeri 2 Tanjung Medang is due to the low learning result of the students' mathematics, from 25 students only 12 students who got the above KKM score of 65 the rest got the value far below KKM. The purpose of the implementation of this research are: to improve the learning outcomes of students of grade V SD Negeri 2 Tanjung Medang by applying interactive learning strategies. The type of research is Classroom Action Research (PTK). Subjects in this study are all students of class V as many as 25 students. Technique used is test and observation. Student learning result data obtained through objective test that is double choice. Observation techniques for measuring teacher and student activity. Research instruments consist of syllabus, lesson plans, student worksheets and observation sheets. This study consists of 2 cycles where each cycle is done with 2 times face-to-face meeting and daily test. Based on observer observer activity of teacher in cycle I meeting 1 get value 71,88 and increase 75 at meeting 2. In cycle II of meeting 1 get value 84,38 and increase become 90,63 at meeting 2. Student activity at cycle 1 meeting 1 obtain value 64.29 and an increase of 67.86 at the meeting 2. In cycle II of meeting 1 got the value of 75 and increased to 82.14 at meeting 2. While student learning outcomes from the initial score of 65.20 increased to 69.60 at the 1st meeting with an increase value of 6.75. At meeting 2 got a value of 75.80 with an increase value of 16.26. This proves that the interactive learning strategy can improve the learning outcomes of students of grade V SD Negeri 2 Tanjung Medang.Keywords: interactive learning strategy, mathematics learning outcomes.